Polymer for power storage device

JP2024079609A5Pending Publication Date: 2026-10-06KAO CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023194655
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-11-30
Filing Date
2023-11-15
Publication Date
2026-10-06

AI Technical Summary

Technical Problem

Conventional binder compositions for power storage devices using silicon-based negative electrode active materials fail to adequately improve charge-discharge cycle characteristics and high-speed discharge capacity retention due to volume changes during charging and discharging, leading to cracking and pulverization of the electrode materials.

Method used

A polymer composition containing a structural unit represented by formula (I) with a content of more than 95% by mass, which enhances adhesion between the negative electrode layer and the current collector, and improves the affinity with silicon-based negative electrode active materials, thereby preventing cracking and promoting high-speed discharge capacity retention.

Benefits of technology

The polymer composition significantly improves the charge/discharge cycle characteristics and high-speed discharge capacity retention of power storage devices, ensuring better adhesion and reducing internal resistance, making it suitable for applications requiring rapid charging and discharging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024079609000001
    Figure 2024079609000001
  • Figure 2024079609000002
    Figure 2024079609000002
Patent Text Reader

Abstract

To provide a polymer for a power storage device that can improve the charge-discharge cycle characteristics and the high-speed discharge capacity maintenance rate of the power storage device having a negative electrode using a silicon-based negative electrode active material.SOLUTION: In one aspect, the present disclosure pertains to a polymer for a power storage device, the polymer containing a structural unit represented by formula (I), and the content of the structural unit represented by the formula (I) being more than 95 mass%. In the formula (I), R1 is a hydrogen atom or a methyl group, R2 is a hydrogen atom, a hydrocarbon group having 1-4 carbon atoms, or a straight-chain or branched-chain hydrocarbon group having 1-4 carbon atoms and having 1-3 hydroxyl groups, and R3 is a straight-chain or branched-chain hydrocarbon group having 1-4 carbon atoms and having 1-3 hydroxyl groups. [Chemical formula 1]SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a polymer for an electricity storage device, a binder composition, a paste for a negative electrode of an electricity storage device, a negative electrode for an electricity storage device, and an electricity storage device. [Background technology]

[0002] The demand for power storage devices has been growing in recent years due to the widespread use of smartphones, zero-emission regulations in the automobile market, and the expanded use of natural energy. Therefore, power storage devices are desired to be small, lightweight, and have large capacity, and there is a growing demand for higher output and higher energy density in automobiles, etc. In response to such demands, the development of power storage devices such as lithium-ion secondary batteries, alkaline-ion secondary batteries, electric double-layer capacitors, and lithium-ion capacitors is being promoted.

[0003] Such an electricity storage device generally has an electrode in which a composite layer containing an active material and the like is applied onto a metal foil, and a binder for electricity storage device electrodes is added to the composite layer to prevent peeling off of the composite layer. Styrene / butadiene rubber (SBR) is the most widely used binder for the negative electrodes of electricity storage devices, but in recent years, development of binders for use in forming composite layers has been progressing with the aim of further improving the performance of electricity storage devices. For example, Patent Document 1 proposes a binder composition containing a graft copolymer having a structure in which a branch polymer containing a water-soluble monomer unit is bonded to a trunk polymer containing a predetermined ratio of hydroxyl group-containing vinyl monomer units and having a weight average molecular weight within a predetermined range. Patent Document 2 proposes a binder composition containing a water-soluble polymer containing a (meth)acrylamide monomer unit and an amine compound. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] International Publication No. 2019 / 159706 [Patent Document 2] International Publication No. 2017 / 130910 Summary of the Invention [Problem to be solved by the invention]

[0005] Graphite-based negative electrode active materials are widely used as the negative electrode active materials for power storage devices, but silicon-based negative electrode active materials have been attracting attention from the viewpoint of increasing capacity. However, silicon-based negative electrode active materials undergo significant volumetric changes due to expansion and contraction during charging and discharging, and it has been recognized that electrodes (negative electrodes) using conventional binder compositions cannot sufficiently improve the charge-discharge cycle characteristics of electricity storage devices. It has also been recognized that an electrode (negative electrode) made using a silicon-based negative electrode active material and a conventional binder composition cannot sufficiently increase the discharge capacity (high-rate discharge capacity) or high-rate discharge capacity retention rate (ratio of discharge capacity during low-rate discharge to high-rate discharge) during charging or discharging at a large current of an electricity storage device. The high-rate discharge capacity retention rate is the ratio of discharge capacity during low-rate discharge to high-rate discharge, and a high high-rate discharge capacity retention rate is a characteristic required for an electricity storage device that requires charging or discharging at a large current. That is, there is still room for improvement in conventional binder compositions in terms of enabling an electricity storage device having a negative electrode using a silicon-based negative electrode active material to exhibit excellent charge-discharge cycle characteristics and a high rate discharge capacity retention rate.

[0006] Therefore, the present disclosure provides a polymer for an electricity storage device that can improve the charge / discharge cycle characteristics and high-rate discharge capacity retention rate of an electricity storage device including a negative electrode that uses a silicon-based negative electrode active material, as well as a binder composition for an electricity storage device, a slurry composition for a negative electrode of an electricity storage device, a negative electrode for an electricity storage device, and an electricity storage device, all of which use the polymer. [Means for solving the problem]

[0007] In one aspect, the present disclosure relates to a polymer for an electricity storage device, which contains a structural unit represented by the following formula (I), and the content of the structural unit represented by the following formula (I) exceeds 95 mass %. [ka] In the formula (I), R 1 is a hydrogen atom or a methyl group, R 2 is a hydrogen atom, a hydrocarbon group having 1 to 4 carbon atoms, or a linear or branched hydrocarbon group having 1 to 4 carbon atoms and having 1 to 3 hydroxyl groups; R 3 is a linear or branched hydrocarbon group having 1 to 4 carbon atoms and containing 1 to 3 hydroxyl groups.

[0008] In one aspect, the present disclosure relates to a binder composition for an electricity storage device, comprising the polymer for an electricity storage device of the present disclosure.

[0009] In one aspect, the present disclosure relates to a paste for a negative electrode of an electricity storage device, comprising a silicon-based negative electrode active material and the polymer for an electricity storage device of the present disclosure.

[0010] In one aspect, the present disclosure relates to a negative electrode for an electricity storage device including a current collector and a composite layer formed on the current collector, the composite layer including a silicon-based negative electrode active material and the polymer for an electricity storage device of the present disclosure.

[0011] The present disclosure relates to an electricity storage device including the electricity storage device negative electrode of the present disclosure. Effect of the Invention

[0012] According to one aspect of the present disclosure, it is possible to provide a polymer for an electricity storage device that can improve the charge / discharge cycle characteristics and high-rate discharge capacity retention rate of an electricity storage device including a negative electrode that uses a silicon-based negative electrode active material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] [Polymers for power storage devices] The present disclosure is based on the finding that, in one or more embodiments, the use of a specific polymer as a binder for an electricity storage device can suppress swelling of the negative electrode that occurs during repeated charging and discharging of an electricity storage device that includes a negative electrode that uses a silicon-based negative electrode active material, thereby improving the battery characteristics of the electricity storage device. That is, in one aspect, the present disclosure relates to a polymer for an electricity storage device (hereinafter also referred to as the "polymer of the present disclosure") that contains a structural unit represented by the above formula (I) (hereinafter also referred to as "structural unit I") and has a content of the structural unit represented by the above formula (I) of more than 95 mass%. In one or more embodiments, the polymer of the present disclosure is a polymer composition for an electricity storage device that contains a polymer that contains structural unit I and has a content of structural unit I of more than 95 mass%. According to the polymer of the present disclosure, in one or a plurality of embodiments, it is possible to improve the charge / discharge cycle characteristics of an electricity storage device including a negative electrode using a silicon-based negative electrode active material.

[0014] The mechanism by which the effects of the present disclosure are manifested is not clear, but is presumed to be as follows. Silicon-based negative electrode active materials expand and contract during charging and discharging, with the theoretical volume change exceeding 300%. This volume change is thought to cause the silicon-based negative electrode active material to crack and shatter, and to cause the coating (SEI) formed on the surface of the silicon-based negative electrode active material to fall off. It is believed that the polymer of the present disclosure, containing the constitutional unit I represented by the above formula (I), exhibits high adsorption to silicon-based negative electrode active materials and can suppress cracking and crushing of the silicon-based negative electrode active material and separation of the SEI that accompanies charge and discharge. In addition, the polymer of the present disclosure is believed to improve the adhesion between the negative electrode layer (mixture layer) and the current collector, and between silicon-based negative electrode active materials, thereby improving the strength of the electrode (silicon-based negative electrode). Furthermore, when the content of the structural unit I in all the structural units of the polymer of the present disclosure exceeds a predetermined amount (95% by mass), the above-mentioned adhesion is sufficiently ensured, and it is considered that the result of the charge-discharge cycle test is also good. This is presumably because the structural unit I has a hydroxyl group and an amide bond, which increases the affinity with the silicon-based negative electrode active material, resulting in excellent adhesion between the negative electrode layer (mixture layer) and the current collector, and between the silicon-based negative electrode active materials themselves. In addition, in the case of an electricity storage device using the polymer of the present disclosure, the discharge capacity is good even in a cycle test in which charging and discharging is performed at high speed, so that the high-speed discharge capacity retention rate is high. The polymer of the present disclosure is expected to enable, for example, rapid acceleration of electric vehicles and to be applied to power tools, etc. This is because, in addition to the above-mentioned improvement in affinity and adhesion, the mutual network of amide groups formed when a hydrocarbon group or a hydroxyl group exists in the same molecule is Li + It is presumed that this is due to the fact that it promotes the movement of oxygen and contributes to a decrease in internal resistance. However, it is not necessary to interpret the present invention as being limited to these mechanisms.

[0015] <Structural unit represented by formula (I) (structural unit I)> The polymer of the present disclosure contains a structural unit (structural unit I) represented by the following formula (I): The structural unit I may be one type, or a combination of two or more types. [ka]

[0016] In the formula (I), R 1 is a hydrogen atom or a methyl group, and is preferably a hydrogen atom from the viewpoint of improving the charge-discharge cycle characteristics of an electricity storage device including a negative electrode using a silicon-based negative electrode active material. R 2 is a hydrogen atom, a hydrocarbon group having from 1 to 4 carbon atoms, or a linear or branched hydrocarbon group having from 1 to 4 carbon atoms and having from 1 to 3 hydroxyl groups, and is preferably a hydrogen atom from the viewpoint of improving the charge-discharge cycle characteristics of an electricity storage device having a negative electrode using a silicon-based negative electrode active material. R 3is a linear or branched hydrocarbon group having 1 to 4 carbon atoms and having 1 to 3 hydroxyl groups, and from the viewpoint of improving the charge-discharge cycle characteristics of an electricity storage device equipped with a negative electrode using a silicon-based negative electrode active material, a linear or branched hydrocarbon group having 2 to 3 carbon atoms and one hydroxyl group is preferred, and a linear hydrocarbon group having 2 carbon atoms and one hydroxyl group is more preferred.

[0017] The content of structural unit I in all structural units of the polymer of the present disclosure is more than 95 mass%, preferably 98 mass% or more, more preferably 99 mass% or more, and even more preferably 100 mass%, from the viewpoint of improving the charge-discharge cycle characteristics of an electricity storage device including a negative electrode using a silicon-based negative electrode active material.

[0018] Examples of monomers that form the structural unit I include at least one selected from N-hydroxymethylacrylamide, N-hydroxyethylacrylamide, N-(2-hydroxypropyl)acrylamide, N-hydroxymethylmethacrylamide, N-hydroxyethylmethacrylamide, N-(2-hydroxypropyl)methacrylamide, and N-[tris(hydroxymethyl)methyl]acrylamide. From the viewpoint of improving the charge-discharge cycle characteristics of an electricity storage device equipped with a negative electrode using a silicon-based negative electrode active material, at least one selected from N-hydroxyethylacrylamide and N-(2-hydroxypropyl)acrylamide is preferred, and N-hydroxyethylacrylamide is more preferred.

[0019] <Other building blocks (building block II)> The polymer of the present disclosure may further include a structural unit (hereinafter also referred to as "structural unit II") other than the structural unit I. The content of the structural unit II in all structural units of the polymer of the present disclosure is less than 5 mass%, preferably 2 mass% or less, more preferably 1 mass% or less, and even more preferably 0 mass%, from the viewpoint of improving the charge-discharge cycle characteristics of an electricity storage device including a negative electrode using a silicon-based negative electrode active material. Examples of monomers that form the structural unit II include acid monomers such as (meth)acrylic acid, (meth)acrylic acid ester monomers, and (meth)acrylamide monomers other than the monomers that form the structural unit I. Examples of (meth)acrylic acid ester monomers include polyethylene glycol (meth)acrylate and alkyl (meth)acrylates having 12 or less carbon atoms. Examples of (meth)acrylamide monomers other than the monomers that form the structural unit I include dimethylacrylamide, diacetoneacrylamide, and tert-butylacrylamide.

[0020] Examples of the polymer of the present disclosure include at least one selected from a hydroxyethylacrylamide polymer, a hydroxyethylacrylamide / polyethylene glycol (meth)acrylate copolymer, and a hydroxyethylacrylamide / acrylic acid copolymer.

[0021] The polymer of the present disclosure can be produced, for example, by polymerizing a monomer that forms the structural unit I and, if necessary, a monomer that forms the structural unit II. Examples of the polymerization method include known polymerization methods such as emulsion polymerization, solution polymerization, suspension polymerization, and bulk polymerization.

[0022] The weight average molecular weight of the polymer of the present disclosure is preferably 50,000 or more, more preferably 100,000 or more, even more preferably 300,000 or more, and even more preferably 500,000 or more from the viewpoint of adhesion between the silicon-based negative electrode active material and the current collector, and is preferably 3,000,000 or less, more preferably 2,000,000 or less, and even more preferably 1,000,000 or less from the viewpoint of handleability of the negative electrode paste. In the present disclosure, the weight average molecular weight is a value measured by gel permeation chromatography (GPC), and the details of the measurement conditions are as shown in the Examples.

[0023] In one or more embodiments, the polymer of the present disclosure can be used as a binder for a negative electrode of an electricity storage device. That is, in one aspect, the present disclosure relates to use of the polymer of the present disclosure as a binder for a negative electrode of an electricity storage device.

[0024] [Binder composition for power storage device] In one aspect, the present disclosure relates to a binder composition for an electricity storage device (hereinafter also referred to as the "binder composition of the present disclosure") that contains the polymer of the present disclosure. In one or more embodiments, the binder composition of the present disclosure can improve the charge-discharge cycle characteristics of an electricity storage device that includes a negative electrode using a silicon-based negative electrode active material.

[0025] <Polymer> The polymer of the present disclosure contained in the binder composition of the present disclosure may be one type or a combination of two or more types. The content of the polymer of the present disclosure in the binder composition of the present disclosure is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more from the viewpoint of compatibility during electrode production, and is preferably 50% by mass or less, more preferably 45% by mass or less, and even more preferably 40% by mass or less from the viewpoint of suppressing a decrease in handleability due to an increase in viscosity. When the polymer of the present disclosure is a combination of two or more types, the content of the polymer of the present disclosure is the total content thereof.

[0026] <Solvent> In one or more embodiments, the binder composition of the present disclosure is a solution containing the polymer of the present disclosure and contains a solvent. The solvent may be water.

[0027] <Other ingredients> The binder composition of the present disclosure may contain other components in addition to the polymer and solvent of the present disclosure, as long as the effects of the present disclosure are not impaired. Examples of other components include at least one selected from a surfactant, a thickener, a defoamer, a dispersant, a preservative, and a neutralizer.

[0028] The binder composition of the present disclosure can be prepared, for example, by mixing the polymer of the present disclosure and, if necessary, the other components described above in a solvent by a known method, for example, a ball mill, a bead mill, an ultrasonic disperser, etc.

[0029] [Paste for negative electrodes of energy storage devices] The polymer of the present disclosure and the binder composition of the present disclosure can be used to prepare a paste for a negative electrode of an electricity storage device. That is, in one aspect, the present disclosure relates to a paste for a negative electrode of an electricity storage device (hereinafter also referred to as the "negative electrode paste of the present disclosure") that contains a silicon-based negative electrode active material and the polymer of the present disclosure. In one or more embodiments, the negative electrode paste of the present disclosure contains a silicon-based negative electrode active material and the binder composition of the present disclosure. In one or more embodiments, the negative electrode paste of the present disclosure is a silicon-based negative electrode paste for a storage battery (silicon-based negative electrode paste). According to the negative electrode paste of the present disclosure, the charge and discharge cycle characteristics of an electricity storage device including a negative electrode using a silicon-based negative electrode active material can be improved.

[0030] <Silicon-based negative electrode active material> In one or more embodiments, the silicon-based negative electrode active material may be silicon (Si), an alloy containing silicon, SiO, SiO x Alternatively, a Si-containing material coated with conductive carbon or composited with conductive carbon may be used. The silicon-based negative electrode active material may be one type or a combination of two or more types. The average particle size of the silicon-based negative electrode active material is preferably 0.01 μm or more, more preferably 0.15 μm or more, and even more preferably 0.5 μm or more, from the viewpoint of improving the charge-discharge cycle characteristics of the power storage device, and is preferably 20 μm or less, more preferably 10 μm or less, and even more preferably 5 μm or less, from the viewpoint of improving the charge-discharge cycle characteristics of the power storage device. The average particle size of the silicon-based negative electrode active material is the volume average particle size (D 50 ) and refers to the particle size at the point where the cumulative volume from the small particle size side is 50% in the cumulative volume distribution curve, where the total volume of the particle size distribution calculated on a volume basis is 100%. 50 ) can be measured using a laser diffraction / scattering type particle size distribution measuring device, specifically, by the method described in the Examples. The content of the silicon-based negative electrode active material in the negative electrode paste of the present disclosure is preferably 0.5 mass% or more, more preferably 1.5 mass% or more, and even more preferably 2 mass% or more from the viewpoint of increasing the capacity of the power storage device, and is preferably 70 mass% or less, more preferably 40 mass% or less, and even more preferably 20 mass% or less from the viewpoint of improving the charge / discharge cycle characteristics of the power storage device. When the silicon-based negative electrode active material of the present disclosure is a combination of two or more types, the content of the silicon-based negative electrode active material in the negative electrode paste of the present disclosure is the total content thereof.

[0031] <Polymer> The negative electrode paste of the present disclosure may contain one type of polymer of the present disclosure, or a combination of two or more types. The content of the polymer of the present disclosure in the negative electrode paste of the present disclosure is preferably 0.1 mass% or more, more preferably 0.3 mass% or more, and even more preferably 0.5 mass% or more from the viewpoint of adhesion between the polymer and the current collector, and is preferably 10 mass% or less, more preferably 5 mass% or less, and even more preferably 3 mass% or less from the viewpoint of increasing the capacity of the electricity storage device. When the polymer of the present disclosure is a combination of two or more types, the content of the polymer of the present disclosure in the negative electrode paste of the present disclosure is the total content thereof. The content ratio of the silicon-based negative electrode active material to the polymer of the present disclosure in the negative electrode paste of the present disclosure is, from the viewpoint of adhesion between the silicon-based negative electrode active material and the current collector, preferably 0.1 part by mass or more, more preferably 1 part by mass or more, and even more preferably 5 parts by mass or more, per 100 parts by mass of the silicon-based negative electrode active material, and from the viewpoint of increasing the capacity of the electricity storage device, preferably 200 parts by mass or less, more preferably 100 parts by mass or less, and even more preferably 50 parts by mass or less.

[0032] <Dispersion medium> In one or more embodiments, the negative electrode paste of the present disclosure includes a dispersion medium. Examples of the dispersion medium include water.

[0033] <Other ingredients> The negative electrode paste of the present disclosure may contain other components in addition to the above-mentioned components. In one or more embodiments, the other components may include a negative electrode active material other than a silicon-based negative electrode active material, a conductive material, a thickener, and the like. Examples of the negative electrode active material other than the silicon-based negative electrode active material include graphite-based negative electrode active materials such as graphite. When the negative electrode paste of the present disclosure contains a graphite-based negative electrode active material, the content of the graphite-based negative electrode active material in the negative electrode paste of the present disclosure is preferably 0.5 mass% or more, more preferably 5 mass% or more, and even more preferably 10 mass% or more from the viewpoint of improving the charge-discharge cycle characteristics of the power storage device, and is preferably 70 mass% or less, more preferably 60 mass% or less, and even more preferably 50 mass% or less from the viewpoint of increasing the capacity of the power storage device. When the graphite-based negative electrode active material is a combination of two or more types, the content of the graphite-based negative electrode active material in the negative electrode paste of the present disclosure is the total content thereof. The conductive material may be any known conductive material that can be used in an electricity storage device, such as acetylene black, ketjen black, graphite, carbon materials such as carbon nanotubes, etc. When the negative electrode paste of the present disclosure contains a conductive material, the content of the conductive material in the negative electrode paste of the present disclosure is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and even more preferably 0.2% by mass or more from the viewpoint of the resistance of the electricity storage device, and is preferably 2% by mass or less, more preferably 1.5% by mass or less, and even more preferably 1% by mass or less from the viewpoint of increasing the capacity of the electricity storage device. When the conductive material is a combination of two or more types, the content of the conductive material in the negative electrode paste of the present disclosure is the total content thereof. Examples of thickeners include carboxymethylcellulose (CMC). When the negative electrode paste of the present disclosure contains a thickener, the content of the thickener in the negative electrode paste of the present disclosure is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, and even more preferably 0.5% by mass or more from the viewpoint of the coatability of the negative electrode paste, and is preferably 2% by mass or less, more preferably 1.5% by mass or less, and even more preferably 1% by mass or less from the viewpoint of increasing the capacity of the power storage device. When the thickener is a combination of two or more types, the content of the thickener in the negative electrode paste of the present disclosure is the total content thereof.

[0034] The solids concentration in the negative electrode paste of the present disclosure is preferably 20% by mass or more, more preferably 30% by mass or more, and even more preferably 35% by mass or more from the viewpoint of productivity of the electricity storage device, and is preferably 80% by mass or less, more preferably 70% by mass or less, and even more preferably 60% by mass or less from the viewpoint of handleability of the negative electrode paste.

[0035] <Method of Preparing Negative Electrode Paste of the Present Disclosure> The negative electrode paste of the present disclosure can be prepared by mixing a silicon-based negative electrode active material, a polymer of the present disclosure, a dispersion medium, and other components as necessary. Examples of the mixing method include a method using a ball mill, a bead mill, an ultrasonic disperser, etc.

[0036] [Anodes for energy storage devices] The polymer of the present disclosure, the binder composition of the present disclosure, and the negative electrode paste of the present disclosure can be used to produce a composite layer of an electrode (negative electrode) for an electricity storage device. That is, in one aspect, the present disclosure relates to a negative electrode for an electricity storage device (hereinafter also referred to as the "negative electrode of the present disclosure") that includes a current collector and a composite layer formed on the current collector, the composite layer including a silicon-based negative electrode active material and a polymer of the present disclosure. In one or more embodiments, the composite layer in the negative electrode of the present disclosure includes a silicon-based negative electrode active material and a binder composition of the present disclosure. The negative electrode of the present disclosure can improve the charge and discharge cycle characteristics of an electricity storage device that includes a negative electrode using a silicon-based negative electrode active material.

[0037] <Current collector> The current collector can be selected from materials having electrical conductivity, and examples thereof include metal foils such as copper foil, nickel foil, aluminum foil, and stainless steel foil.

[0038] <Mixture layer> The mixture layer can be obtained, for example, by applying the negative electrode paste of the present disclosure containing a silicon-based negative electrode active material and the polymer of the present disclosure onto a current collector, and then drying and removing the solvent in the negative electrode paste. The method for applying the negative electrode paste (slurry) to the current collector can be a known application method, such as a gravure method, a reverse roll method, a direct roll method, or a doctor blade method. The negative electrode paste may be applied to only one side of the current collector or to both sides of the current collector. The thickness of the coating film can be appropriately set depending on the thickness of the mixture layer obtained after drying. The negative electrode paste can be dried by a known drying method, for example, drying using hot air or the like, vacuum drying, drying using infrared radiation or the like. In one or more embodiments, the composite layer contains a silicon-based negative electrode active material, a polymer according to the present disclosure, and other components as necessary. Examples of the other components include the same components as those of the negative electrode paste according to the present disclosure described above. (Silicon-based negative electrode active material) The content of the silicon-based negative electrode active material in the mixture layer is preferably 1% by mass or more, more preferably 3% by mass or more, and even more preferably 5% by mass or more from the viewpoint of ensuring the battery energy density, and is preferably 99.8% by mass or less, more preferably 80% by mass or less, even more preferably 50% by mass or less, and even more preferably 30% by mass or less from the viewpoint of suppressing deterioration of the negative electrode due to expansion and contraction of the silicon-based negative electrode active material. When the silicon-based negative electrode active material is a combination of two or more types, the content of the silicon-based negative electrode active material in the mixture layer is the total content thereof. (Polymer) The content of the polymer of the present disclosure in the mixture layer is preferably 0.2% by mass or more, more preferably 0.5% by mass or more, and even more preferably 1% by mass or more from the viewpoint of adhesion between the silicon-based negative electrode active material and the current collector, and is preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less from the viewpoint of increasing the capacity of the power storage device. When the polymer of the present disclosure is a combination of two or more kinds, the content of the polymer of the present disclosure in the mixture layer is the total content thereof. Regarding the content ratio of the silicon-based negative electrode active material and the polymer of the present disclosure in the composite layer, the content of the polymer of the present disclosure is preferably 0.1 part by mass or more, more preferably 1 part by mass or more, and even more preferably 10 parts by mass or more, per 100 parts by mass of the silicon-based negative electrode active material, from the viewpoint of adhesion between silicon-based negative electrode active materials, and is preferably 200 parts by mass or less, more preferably 100 parts by mass or less, and even more preferably 50 parts by mass or less, from the viewpoint of increasing the capacity of the electricity storage device. (Other Ingredients) When the composite layer of the present disclosure contains a graphite-based negative electrode active material, the content of the graphite-based negative electrode active material in the composite layer is preferably 1 mass% or more, more preferably 10 mass% or more, and even more preferably 20 mass% or more from the viewpoint of improving the charge / discharge cycle characteristics of the power storage device, and is preferably 98.8 mass% or less, more preferably 97 mass% or less, and even more preferably 95 mass% or less from the viewpoint of increasing the capacity of the power storage device. When the graphite-based negative electrode active material of the present disclosure is a combination of two or more types, the content of the graphite-based negative electrode active material in the composite layer is the total content thereof. When the composite layer of the present disclosure contains a conductive material, the content of the conductive material in the composite layer is preferably 0.02 mass% or more, more preferably 0.2 mass% or more, and even more preferably 0.5 mass% or more from the viewpoint of the resistance of the power storage device, and is preferably 3 mass% or less, more preferably 2.5 mass% or less, and even more preferably 2 mass% or less from the viewpoint of increasing the capacity of the power storage device. When the graphite-based negative electrode active material of the present disclosure is a combination of two or more kinds, the content of the conductive material in the composite layer is the total content thereof. When the mixture layer of the present disclosure contains a thickener, the content of the thickener in the mixture layer is preferably 0.2 mass% or more, more preferably 0.5 mass% or more, and even more preferably 1 mass% or more from the viewpoint of coatability of the negative electrode paste, and is preferably 5 mass% or less, more preferably 3 mass% or less, and even more preferably 2 mass% or less from the viewpoint of increasing the capacity of the power storage device. When the thickener of the present disclosure is a combination of two or more types, the content of the thickener in the mixture layer is the total content thereof.

[0039] [Electricity storage device] In one aspect, the present disclosure relates to an electricity storage device including a negative electrode according to the present disclosure (hereinafter, also referred to as the "electricity storage device according to the present disclosure"). According to the present disclosure, it is possible to provide an electricity storage device having excellent charge / discharge cycle characteristics. In one or a plurality of embodiments, examples of the power storage device according to the present disclosure include a lithium ion secondary battery, a lithium-air secondary battery, a lithium-sulfur secondary battery, a sodium ion secondary battery, a sodium-sulfur secondary battery, a sodium-nickel chloride secondary battery, an organic radical battery, a zinc-air secondary battery, and an all-solid-state battery.

[0040] One or more embodiments of the power storage device of the present disclosure are power storage devices including the negative electrode of the present disclosure and an electrolytic solution. The electrolytic solution may include a solvent and an electrolyte, and examples of the solvent include water, an ionic liquid, or carbonates such as ethylene carbonate (EC) and diethyl carbonate (DEC), and examples of the electrolyte include metal salts, such as lithium salts such as LiPF6. The electricity storage device of the present disclosure can be manufactured by, for example, a known method for manufacturing an electricity storage device, which includes stacking two electrodes (a positive electrode and a negative electrode) with a separator therebetween, winding or stacking them into a battery shape, placing them in a battery container or a laminate container, injecting an electrolyte into the container, and sealing the container.

[0041] The present application further discloses the following polymer for an electricity storage device, binder composition for an electricity storage device, and paste for a negative electrode of an electricity storage device.

[0042] [1] Contains a structural unit represented by the following formula (I): A polymer for an electricity storage device, having a content of a structural unit represented by the following formula (I) of more than 95 mass %: [ka] In the formula (I), R 1 is a hydrogen atom or a methyl group, R 2is a hydrogen atom, a hydrocarbon group having 1 to 4 carbon atoms, or a linear or branched hydrocarbon group having 1 to 4 carbon atoms and having 1 to 3 hydroxyl groups; R 3 is a linear or branched hydrocarbon group having 1 to 4 carbon atoms and containing 1 to 3 hydroxyl groups. [2] R 1 is a hydrogen atom. [3] R 2 is a hydrogen atom. [4] R 3 is a linear hydrocarbon group having one hydroxyl group and having two carbon atoms. [5] The polymer for an electricity storage device according to any one of [1] to [4] above, having a weight average molecular weight of 50,000 or more and 3,000,000 or more. [6] The polymer for an electricity storage device according to any one of [1] to [5] above, wherein the content of the structural unit represented by (I) is 100 mass %. [7] A binder composition for an electricity storage device, comprising the polymer for an electricity storage device according to any one of [1] to [6] above and a solvent. [8] A paste for a negative electrode of an electricity storage device, comprising a silicon-based negative electrode active material and the polymer for a electricity storage device according to any one of [1] to [6] above. [9] A negative electrode for an electricity storage device, comprising: a current collector; and a mixture layer formed on the current collector, The negative electrode for an electricity storage device, wherein the mixture layer contains a silicon-based negative electrode active material and the polymer for an electricity storage device according to any one of [1] to [6].

[10] An electricity storage device comprising the electricity storage device negative electrode according to [9].

[11] Use of the polymer for an electricity storage device according to any one of [1] to [6] above for producing a binder composition for an electricity storage device.

[12] Use of the polymer for an electricity storage device according to any one of [1] to [6] above for the production of a paste for a negative electrode of an electricity storage device.

[13] Use of the polymer for an electricity storage device according to any one of [1] to [6] above for producing a negative electrode for an electricity storage device. EXAMPLES

[0043] The present disclosure will be specifically described below with reference to examples, but the present disclosure is not limited to these examples in any way.

[0044] 1. Synthesis of Polymers A1 to A3 for Electric Storage Devices [Production Example 1: Synthesis of Polymer A1] 363 g of ion-exchanged water was charged into a 1 L four-neck glass separable flask and stirred under a nitrogen atmosphere for 0.5 hours. The solution in the flask was heated to 75°C, and 83 g of a 60% by mass aqueous solution of 50.0 g of N-hydroxyethylacrylamide (KJ Chemicals) and 60 g of a 1% by mass aqueous solution of 0.6 g of 2,2'-azobis(2-methylpropionamidine) dihydrochloride (FUJIFILM Wako Pure Chemical Industries) were dropped into the flask over 1 hour. The solution in the flask was then kept at 75°C for another 4 hours to obtain a polymer solution (polymer A1) of Production Example 1. The polymer concentration in the polymer solution was 10% by mass. The weight-average molecular weight of polymer 1 was 750,000 (Table 1). [Production Examples 2 to 3: Synthesis of Polymers A2 to A3] According to the method of Production Example 1, the polymerizable monomer that forms the structural unit of general formula (1) and the polymerizable monomer that forms the remaining structural unit II shown in Table 1 (PEG 10 -A: Polyethylene glycol acrylate, EO addition mole number 10, "AE-400" manufactured by NOF Corporation was copolymerized to obtain polymer solutions (polymers A2 to A3) of Production Examples 2 to 3. The concentrations of polymers A2 to A3 in the polymer solutions were 10 mass %, respectively. The weight average molecular weights of polymers A2 to A3 are shown in Table 1.

[0045] [Table 1]

[0046] [Measurement of weight average molecular weight] The weight-average molecular weight of the polymer for use in an electricity storage device was measured by gel permeation chromatography (GPC) under the following detailed conditions. <Measurement conditions> Measuring device: HLC-8320GPC (Tosoh Corporation, detector integrated) Column: GMPWXL+GMPWXL (anion, manufactured by Tosoh Corporation) Eluent: 0.2 molar phosphate buffer / acetonitrile (=9 / 1) Flow rate: 0.5mL / min Column temperature: 40℃ Detector: RI detector Standard material: Polyethylene oxide

[0047] 2. Preparation of Silicon-based Negative Electrode Paste Example 1 A slurry [1] was prepared by mixing 0.16 g of a conductive material (acetylene black, Denka, "Li-100"), 5.5 g of a 1.5 mass % aqueous solution of a thickener (sodium carboxymethylcellulose, Fujifilm Wako Pure Chemical Industries, Ltd.), 7.88 g of a graphite-based negative electrode active material (graphite, Showa Denko, "MCMG-CF-C"), and 0.88 g of a silicon-based negative electrode active material (silicon monoxide, Fujifilm Wako Pure Chemical Industries, Ltd.). Next, 3.73 g of a 1.5 mass % aqueous solution of a thickener (sodium carboxymethylcellulose, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) and 0.53 g of ion-exchanged water were added to and mixed with the slurry [1] to prepare a slurry [2]. Next, 1.85 g of the 10 mass% polymer A1 aqueous solution prepared in Production Example 1 was added to prepare the silicon-based negative electrode paste of Example 1. The components were mixed using "Thin Mixer (ARV-310)". The content of each component in the silicon-based negative electrode paste was 0.9 mass% polymer, 4.3 mass% silicon-based negative electrode active material, 38.4 mass% graphite-based negative electrode active material, 0.8 mass% conductive material, and 0.67 mass% thickener. The content of the polymer in the silicon-based negative electrode paste was 21 parts by mass relative to 100 parts by mass of the silicon-based negative electrode active material. The solid content of the silicon-based negative electrode paste was 45 mass%. (Comparative Examples 1 to 2) Silicon-based negative electrode pastes of Comparative Examples 1 and 2 were prepared in the same manner as in the preparation of the silicon-based negative electrode paste of Example 1. The blended composition was the same as in Example 1, and only the type of polymer used was changed.

[0048] 3. Preparation of Silicon-based Negative Electrode 1 A negative electrode with a capacity density of 6 mAh / cm2 was placed on a 20 μm thick copper foil. 2 The silicon-based negative electrode paste was applied so that the coating (thickness 380 μm) was dried at 100 ° C. for 12 hours using a vacuum dryer. As a result, a silicon-based negative electrode (silicon-based negative electrode having a negative electrode mixture layer) in which a composite layer (thickness 120 μm) was formed on the current collector was produced. This was pressed with a press machine to produce a silicon-based negative electrode (silicon-based negative electrode having a negative electrode mixture layer) in which a composite layer (100 μm) was formed on the current collector. The electrode (negative electrode) was produced so that the composition was 85.3 mass% graphite, 9.5 mass% SiO (average particle size: 1 μm), 1.7 mass% conductive material, 1.5 mass% thickener, and 2.0 mass% polymer. [Measurement of the average particle size of silicon-based negative electrode active material] The volume average particle size (D 50 ) was measured.

[0049] 4. Evaluation of negative electrode performance The charge / discharge characteristics of electricity storage devices prepared as described below using the silicon-based negative electrodes of Example 1 and Comparative Examples 1 and 2 were evaluated for negative electrode performance by the following charge / discharge cycle test. [Fabrication of coin cells (electricity storage devices)] Each silicon-based negative electrode was punched out to a diameter of 14 mm and pressed. A separator with a diameter of 19 mm [manufactured by Hosensha] and a coin-shaped lithium foil with a diameter of 15 mm and a thickness of 0.5 mm were placed on the pressed silicon-based negative electrode to prepare a 2032-type coin half cell. The electrolyte used was 1M LiPF6EC / DEC (volume ratio) = 3 / 7. [Charge / discharge cycle test] The coin cell thus produced was subjected to a charge-discharge cycle test at 45°C using an Electrofield charge-discharge tester (ABE1024). Charging consisted of constant current charging at 0.1C from the OCV to 0V, followed by constant voltage charging for 10 minutes. Discharging consisted of constant current discharging at 0.1C to 1.2V. This charge-discharge cycle was repeated 50 times. Note that charging this cell refers to the process of lithium ions being inserted from lithium metal into the silicon-based negative electrode, and discharging refers to the reverse reaction. [Capacity maintenance rate] The above-mentioned charge / discharge cycle test was carried out using the produced coin cell (electricity storage device), and the capacity retention rate was calculated by the following formula. The results are shown in Table 2. Capacity retention rate = (discharge capacity at 50th cycle) / (discharge capacity at 1st cycle)

[0050] [Table 2]

[0051] As shown in Table 2, in Example 1, which used polymer A1 having a content of structural unit I exceeding 95% by mass, the capacity retention rate during charge-discharge cycles was higher than in Comparative Examples 1 and 2, which used polymers A2 and A3 having a content of structural unit I of 95% by mass or less, and it was found that the charge-discharge cycle characteristics of an electricity storage device having a negative electrode using a silicon-based negative electrode active material can be improved.

[0052] 5. Preparation of silicon-based negative electrode 2 (negative electrode for full cell) On a 20 μm thick copper foil, the negative electrode capacity density is 2.1 mAh / cm 2The silicon-based negative electrode paste was applied so that the resultant coating (thickness: 130 μm) was dried at 100° C. for 12 hours using a vacuum dryer. This produced a silicon-based negative electrode (silicon-based negative electrode having a negative electrode mixture layer) in which a mixture layer (thickness: 45 μm) was formed on the current collector. This was pressed with a press machine to produce a silicon-based negative electrode (silicon-based negative electrode having a negative electrode mixture layer) in which a mixture layer (35 μm) was formed on the current collector. The electrode (negative electrode) composition was 85.3% by mass of graphite, 9.5% by mass of SiO (average particle size: 1 μm), 1.7% by mass of conductive material, 1.5% by mass of thickener, and 1.5% by mass of polymer. : It was prepared so that the content was 2.0 mass%.

[0053] 6. Preparation of Positive Electrode for Full Cell 15 g of positive electrode active material (Nippon Chemical Industry Co., Ltd., NCM523), 5.98 g of polyvinylidene fluoride (PVDF) n-methylpyrrolidone (NMP) solution (8% solids KF polymer L#7208, Kureha Corporation, binder solution), 0.48 g of conductive material (acetylene black, Denka Co., Ltd., "Li-100"), and 12.97 g of solvent (NMP) were mixed for 10 minutes in a planetary centrifugal mixer (AR-100, Thinky Corporation) to prepare a positive electrode paste with a solids content of 46% by mass. This was applied to aluminum foil with a thickness of 20 μm and dried at 100° C., resulting in a positive electrode capacity density of 2.0 mAh / cm. 2 A positive electrode was prepared.

[0054] [Production of coin cells (electricity storage devices) (full cells)] A 2032-type coin cell (full cell) was fabricated by punching out the positive electrode with a diameter of 13 mm and the silicon-based negative electrode with a diameter of 14 mm, placing a separator with a diameter of 19 mm [manufactured by Hosen Co., Ltd.] on the positive electrode, and then placing the silicon-based negative electrode as a counter electrode. The electrolyte used was 1M LiPF6EC / DEC (volume ratio) = 3 / 7.

[0055] [Full cell evaluation] The resulting full cell was used to measure the battery characteristics (rate characteristics 5C). Specifically, the battery was charged to 4.2V at 0.1C according to the following conditions in an environment of 25°C, and then discharged to 3V at 0.1C to determine the discharge capacity. The 5C discharge capacity was then determined in the same manner, and the 5C discharge capacity retention rate was calculated based on the 0.1C discharge capacity. (Charging conditions) 0.1C CC―CV4.2V(0.02C Cut off) (Discharge conditions) 0.1C or 5C CC (3V Cut off) High-speed discharge capacity retention rate (%) = (5C discharge capacity / 0.1C discharge capacity) x 100

[0056] [Table 3]

[0057] As shown in Table 3, Example 1, which used polymer A1 having a content of structural unit I exceeding 95% by mass, had a higher high-rate discharge capacity retention rate than Comparative Examples 1 and 2, which used polymers A2 and A3 having a content of structural unit I of 95% by mass or less, and it was found that the high-rate discharge capacity retention rate characteristics of an electricity storage device having a negative electrode using a silicon-based negative electrode active material can be improved. [Industrial Applicability]

[0058] The polymer for an electricity storage device according to the present disclosure can be used, for example, in various electricity storage devices.

Claims

1. It includes the constituent units represented by the following formula (I), A paste for an anode of an energy storage device, comprising a polymer for energy storage devices having a content of more than 95% by mass of the constituent unit represented by the following formula (I), and a silicon-based anode active material. 【Chemistry 1】 In the above formula (I), R 1 R is a hydrogen atom or a methyl group, 2 R is a straight-chain or branched-chain hydrocarbon group having 1 to 4 carbon atoms, which has a hydrogen atom, a hydrocarbon group having 1 to 4 carbon atoms, or a hydrocarbon group having 1 to 3 hydroxyl groups. 3 This refers to a straight-chain or branched hydrocarbon group having 1 to 4 carbon atoms and possessing 1 to 3 hydroxyl groups.

2. The paste for the negative electrode of an energy storage device according to claim 1, wherein R1 is a hydrogen atom.

3. The paste for the negative electrode of an energy storage device according to claim 1 or 2, wherein R2 is a hydrogen atom.

4. The paste for the negative electrode of an energy storage device according to claim 1 or 2, wherein R3 is a linear hydrocarbon group having one hydroxyl group and having 2 carbon atoms.

5. The paste for the negative electrode of an energy storage device according to claim 1 or 2, wherein the weight-average molecular weight of the polymer for the energy storage device is 50,000 or more and 3,000,000 or more.

6. The paste for the negative electrode of an energy storage device according to claim 1 or 2, wherein the polymer for the energy storage device contains 100% by mass of the constituent unit represented by formula (I).

7. The paste for the negative electrode of an energy storage device according to claim 1 or 2, wherein the average particle size of the silicon-based negative electrode active material is 0.01 μm or more and 20 μm or less.

8. The paste for the negative electrode of an energy storage device according to claim 1 or 2, wherein the content of the silicon-based negative electrode active material is 0.5% by mass or more and 70% by mass or less.

9. The paste for the negative electrode of an energy storage device according to claim 1 or 2, comprising water as a dispersion medium.

10. A negative electrode for an energy storage device, comprising a current collector and a composite material layer formed on the current collector, The composite layer comprises a silicon-based negative electrode active material and a polymer for energy storage devices, wherein the polymer contains a component represented by the following formula (I), and the content of the component represented by the following formula (I) exceeds 95% by mass. 【Chemistry 2】 In formula (I), R1 is a hydrogen atom or a methyl group, R2 is a hydrogen atom, a hydrocarbon group having 1 to 4 carbon atoms, or a linear or branched hydrocarbon group having 1 to 4 carbon atoms having 1 to 3 hydroxyl groups, and R3 is a linear or branched hydrocarbon group having 1 to 4 carbon atoms having 1 to 3 hydroxyl groups.

11. A power storage device comprising a negative electrode for a power storage device as described in claim 10.